Coordination and self-organization in minority games: Experimental evidence - Giulio Bottazzi; Giovanna Devetag (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
This work presents experimental results on a coordination game in which agents must repeatedly choose between two sides, and a positive fixed payoff is assigned only to agents who pick the minoritarian side. We conduct laboratory experiments in which stationary groups of five players play the game for 100 periods, and manipulate two treatment variables: the amount of 'memory' M that players have regarding the game history (i.e., the length of the string of past outcomes that players can see on the screen while choosing), and the amount of information about other players' past choices. Our results show that, at the aggregate level a quite remarkable degree of coordination is achieved. Moreover providing players with full information about other players' choice distribution does not appear to improve efficiency significantly. At the individual level, a substantial portion of subjects exhibit 'inertial' behavior.
Keywords: 330; Test; Theorie; Wiederholte Spiele; Koordination; Selbstorganisation